The Impact of Online Learning on Student Learning Outcomes in the Digital Era - Heti Susanti; AMohd Hafizan Bin Hashim; Rahayu Meliasari; Utin Holanita; Abang Sudarso; Rivanka Elza Pratiwi; Sari Syahfani; Saskia Maharani; Seli Marselina; Syarifudin Mahfud; Winne Averline; Yesha Patrissia; Yogi Syaputra; Yennie Octavia; Iqzzy Salsabila (Universitas PGRI Pontianak, 2025)
The fast growth of information and communication technology in the digital age has changed how we learn. One change is the rise of Online Learning as a useful option for learning. This study aims to deeply understand how Online Learning affect students' learning results. Using a quantitative approach, we collected data through a questionnaire from students chosen based on their experiences with different Online Learning. The data analysis focused on exploring their experiences, views, and opinions about the effectiveness, challenges, and benefits of online learning for their academic understanding. The results are expected to give clear insights into the role of online learning platforms in higher education today.